Enhancing the Conductivity of Cell-Laden Alginate Microfibers With Aqueous Graphene for Neural Applications - McNamara, Marilyn C.; Niaraki-Asli, Amir Ehsan; Guo, Jingshuai; Okuzono, Jasmin; Montazami, Reza; Hashemi, Nicole N. (Frontiers in Materials, 2020)
Microfluidically manufacturing graphene-alginate microfibers create possibilities for encapsulating rat neural cells within conductive 3D tissue scaffolding to enable the creation of real-time 3D sensing arrays with high physiological relavancy. Cells are encapsulated using the biopolymer alginate, which is combined with graphene to create a cell-containing hydrogel with increased electrical conductivity. Resulting novel alginate-graphene microfibers showed a 2.5-fold increase over pure alginate microfibers, but did not show significant differences in size and porosity. Cells encapsulated within the microfibers survive for up to eight days, and maintain approximately 20% live cells over that duration. The biocompatible aqueous graphene suspension used in this investigation was obtained via liquid phase exfoliation of pristine graphite, to create a graphene-alginate pre-hydrogel solution.